The desire to migrate : a case study of the image of the primate city among rural youths in Thailand - Boonma Nakornint; Goede, J.H. de; Angel, Shlomo; Exell, Robert H.B.; The United Kingdom Government (Bangkok : Asian Institute of Technology, 1976)
The purpose of this study are to understand the image that the rural youths have of Bangkok, to determine what channels of information affect the image, and to find out whether or not the rural youths' image of Bangkok is related to their desire to migrate to Bangkok. In an attempt to understand the rural youths' image of Bangkok, Hersh berger's concept of"Architectural Meaning" has been applied. Data analysis was based on field data collected from the seventh-grade students of schools under the provincial authority in amphoe Tha Maka, Kanchanaburi province. Field data included personal interviews, interpretation of a composite photograph of Bangkok, and student drawing of Bangkok. Findings indicate that rural youths imagine Bangkok as having both negative and positive characteristics. The main attributes of Bangkok's Physical Image are: many slums, polluted areas, heavy traffic, overcrowding high buildings, many street intersections, higher quality dwelling units, and modern living. Its Social Image is characterized by many crimes and robberies, fires, accidents, troubles and demonstrations. Its Economic Image includes unemployment, heavier competition, possibilities at get rich quicker. The most effective channels of information on the rural youths' images are: their own experiences of Bangkok, daily newspapers, radio, television set, and their friends and relatives in Bangkok. The images the rural youths have of Bangkok are slightly related to their desire to migrate. Their desire to migrate is strongly associated with their perception of job-opportunities in Bangkok. Furthermore, although educational and occupational aspirations are not related to the desire to migrate to Bangkok, they appear to increase probabilities of migration, as most tend to move away from farming and towards
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science of the Asian Institute of Technology, Bangkok, Thailand
Thesis (M.Sc.) - Asian Institute of Technology, 1976
Keywords: Rural-urban migration -- Thailand